2019
DOI: 10.1200/jco.2019.37.15_suppl.e20657
|View full text |Cite
|
Sign up to set email alerts
|

Immune related adverse events in NSCLC patients treated with immune checkpoint therapy who received the influenza vaccination versus no vaccination.

Abstract: e20657 Background: Influenza vaccination is recommended by the CDC for cancer patients to reduce the risk of influenza-related complications. There is concern that the incidence of immune-related adverse events (irAEs) may be greater in vaccinated patients receiving immune checkpoint inhibitors (ICPI). We sought to interrogate if influenza vaccination in patients with NSCLC receiving ICPI therapy had an increased incidence of irAEs compared to non-vaccinated patients. Methods: We conducted a single-center ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Safety outcomes : three studies reported data regarding vaccine-related adverse events, however, not comparing influenza vaccinated versus nonvaccinated patients29,34,36; thus, a meta-analysis was not feasible. Regarding irAEs, 6 studies (n=1285, weighted age 60 y, men 59%, influenza vaccinated 48%) reported relevant data 30,33,38,44–46. Meta-analysis of these studies showed pooled OR for any irAEs in influenza vaccinated versus nonvaccinated patients at 0.82 (95% CI: 0.63–1.08, P =NS) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Safety outcomes : three studies reported data regarding vaccine-related adverse events, however, not comparing influenza vaccinated versus nonvaccinated patients29,34,36; thus, a meta-analysis was not feasible. Regarding irAEs, 6 studies (n=1285, weighted age 60 y, men 59%, influenza vaccinated 48%) reported relevant data 30,33,38,44–46. Meta-analysis of these studies showed pooled OR for any irAEs in influenza vaccinated versus nonvaccinated patients at 0.82 (95% CI: 0.63–1.08, P =NS) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among 1046 articles initially retrieved, 25 were found to fulfill the inclusion criteria and were included in the systematic review 19,20,29–50. Fourteen studies were peer-reviewed19,20,29–40 and 11 nonpeer-reviewed (conference abstracts) 41–50.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations